A swarm intelligence-based approach for addressing network partitioning constraints in mobile ad hoc networks. (1st January 2015) - Sumathy, S.; Saravanan, R.
Recent trends in wireless communication show an increase in use of mobile devices to exchange information. Due to frequent mobility, there is a possibility that the devices in the network may move out of the transmission range and may fail to connect to the network. To ensure network connectivity in these situations, researchers have proposed many methodologies to determine optimal location for placing mobile forwarding nodes such as particle swarm optimisation, ant colony etc., that helps in establishing routes effectively. A method that establishes an optimal route using genetic algorithm after determining an effective location using particle swarm optimisation is proposed. The proposed work focuses on integrating the benefits of particle swarm optimisation to determine optimal location for placing mobile forwarding node with genetic algorithm to establish an optimal route to destination. Performance of the proposed methodology when analysed using the simulation studies reveals that the packet drop rate is reduced and throughput is improved significantly.